Exploring Preservice Teachers’ Perceived Emotions, Professional Accountability, and Action-Taking Dispositions Towards Language Assessment Scenarios - Claudio Díaz Larenas; Mabel Ortiz Navarrete; Tania Tagle Ochoa; Juan Fernando Gómez Paniagua; Marcela Quintana Lara; Lucia Ramos Leiva; Rocío Acevedo Rivera (Education Sciences)
This exploratory case study investigates the emotional responses, professional accountability, and action-taking dispositions of 150 Chilean prospective English as a Foreign Language (EFL) teachers towards language assessment scenarios. Despite the growing interest in assessment, little research has focused on the affective experiences of trainee teachers. Participants completed the Emotionally Loaded Situations Questionnaire, which assessed their reactions to situations where students fail language assessments. The study reveals that these situations elicited negative emotional responses, leading to a diminished sense of teacher identity due to perceived inefficiencies in teaching and assessment practices. The findings also highlight the teachers’ dispositions towards taking corrective actions, such as revisiting teaching and assessment strategies, reinforcing assessment content, and improving future practices. As to professional accountability, trainee teachers acknowledge that their teaching performance has a direct effect on their students’ assessment results. These outcomes emphasize the need for further research on the affective dimension in language assessment to better support the professional development of future teachers.